Asprosin in health and disease, a new glucose sensor with central and peripheral metabolic effects - Farrag, Mariam; Ait Eldjoudi, Djedjiga; González-Rodríguez, María; Cordero-Barreal, Alfonso; Ruiz-Fernández, Clara; Capuozzo, Maurizio; González-Gay, Miguel Angel; Mera, Antonio; Lago, Francisca; Soffar, Ahmed; Essawy, Amina; Pino, Jesus; et al. (Frontiers in Endocrinology, 2023)
Adipose tissue malfunction leads to altered adipokine secretion which might consequently contribute to an array of metabolic diseases spectrum including obesity, diabetes mellitus, and cardiovascular disorders. Asprosin is a novel diabetogenic adipokine classified as a caudamin hormone protein. This adipokine is released from white adipose tissue during fasting and elicits glucogenic and orexigenic effects. Although white adipose tissue is the dominant source for this multitask adipokine, other tissues also may produce asprosin such as salivary glands, pancreatic B-cells, and cartilage. Significantly, plasma asprosin levels link to glucose metabolism, lipid profile, insulin resistance (IR), and β-cell function. Indeed, asprosin exhibits a potent role in the metabolic process, induces hepatic glucose production, and influences appetite behavior. Clinical and preclinical research showed dysregulated levels of circulating asprosin in several metabolic diseases including obesity, type 2 diabetes mellitus (T2DM), polycystic ovarian syndrome (PCOS), non-alcoholic fatty liver (NAFLD), and several types of cancer. This review provides a comprehensive overview of the asprosin role in the etiology and pathophysiological manifestations of these conditions. Asprosin could be a promising candidate for both novel pharmacological treatment strategies and diagnostic tools, although developing a better understanding of its function and signaling pathways is still needed.